Estudo sobre aplicação de web semântica e visualização em dados abertos: proposta de portal para transparência em séries históricas de indicadores sociais, econômicos e financeiros, públicos na web - Garcia, Paulo Sérgio Rangel (2011)
This paper aims to discuss a model for constructing a transparent portal that contains historical trends of public social, economical and financial indicators, preferably if collected at e-Gov websites. In order to reach that objective, we researched extensively within Manuel Castells, Tim Berners-Lee, Vinton Cerf, Karin K. Breitman, Martha Gabriel and Fernanda Viegas s work, amongst others, about semantic web, ontologies, search engine optimization and data visualization. Starting from a study of the historical evolution of internet, we try to understand how was possible to forge this context of highly productive disorganized dynamics that provided the conditions of the massive availability of information and data that we see today. By utilizing concepts and technologies such as metadata, ontologies, web services, software agents, data visualization and optimization of research mechanisms, we discuss techniques and methodologies that could make collecting data as fast as possible feasible, as well as putting it together in a way that either humans or other computer systems may easily understand. We also analyze the current e-Gov services provided by the Brazilian government by evaluating its characteristics, tendencies and possibilities for evolution and growth by utilizing data and research provided by NIC.BR and W3C BR. Thus, based on research and the author s own experience, this dissertation will try to propose a model for a portal that allows human interaction and integration with other computer systems for historical trends collected via web and formats and provides this data to society in a structured way. Finally, we indicate future researches that may contribute to the discussion and development of websites and services that apropriate public open data